(untitled) (The Peerian Journal, 2024)
regarding the four properties, and discussed the potential for AI to enhance the resistance of RAS to corrosion. While we discuss the benefits of AI to humans, there are also negative consequences that need to be understood. The new idea of human-centered artificial intelligence will serve as the catalyst for the implementation of a dependable RAS. This survey can be employed to explore additional research on the four properties of dependable RAS, it also discussed the potential for AI to enhance the efficacy of RAS. While we discuss the benefits of AI to humans, we also need to understand the potential dangers associated with it. The new idea of human-centered AI will serve as the impetus for the implementation of a dependable RAS.